FASTENING TRANSFER OF TECHNOLOGY THROUGH THE FRANCHISE AGREEMENT - Asikin, Zainal (Jurnal IUS (Kajian Hukum dan Keadilan), 2014)
The major improvement of franchise practices in Indonesian within the last 10 (ten) years has speeded to many region. Yet the government and local government under informed about the exact concept and regulation of franchise. Therefore this research meant to find out the concept of franchise and how the government regulate franchise agreement and its relation with transfer of technology. This research in a normative research as a way to depth study legal norms in various primary and secondary legal sources in Indonesia. In fact, in Indonesian the practice of franchise has developed widely without having a particular law to regulate formulate a law to regulate franchise particularly, as the regulation in form of governmentÂ  regulation (PP No. 42 of 2007) is inadequate to solve the complex legal problem of franchise practice.Keyword : franchise, agreement, transfer of technology